The Role of Financial Performance in Increasing Environmental Performance with Firm Size as Moderating Variable - Tri Handayani, Elfa Dikah; Wahyudin, Agus (Accounting Analysis Journal, 2020)
This study aims to analyze and obtain empirical evidence about the effect of profitability and leverage on environmental performance with size as a moderating variable. This research is a quantitative study with data collection technique through documentation in the form of annual financial reports. The population of this study is 143 manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2016-2018. Based on purposive sampling technique were obtained a sample of 65 companies and 195 analysis units. The data analysis technique used is moderated regression analysis (MRA) with IBM SPSS 25 software. This study found a significant negative effect between profitability and leverage on environmental performance and firm size is able to moderate the effect of profitability and leverage on environmental performance. Based on the results, this study concludes that the large company will try to improve their environmental performance when profitability and leverage conditions increase or decrease. Future research is suggested to use the amount of carbon produced, the amount of water used, and the number of work accidents as a measurement of environmental performance. Keywords: Profitability; Leverage; Environmental Performance; Size; Financial Performance